AN ANALYSIS OF DISCOURSE STRUCTURE OF BROMO PODCAST IN YOUTUBE CHANNEL - Juli, Juli; Tjahyadi, Indra (JURNAL LITERASI, 2023)
This research is about the study of discourse in the Bromo Podcast Episode podcast "Apa dan Bagaimana KPU Kabupaten Probolinggo?” on KPU Kabupaten Probolinggo Youtube Channel, this study aims to determine the microstructure, superstructure, and microstructure of the podcast. This research uses Van Dijk's theory, which is about the structure of discourse. Based on the research results that this podcast found the theme, structure, and language style of the speakers, it can be observed from several statements made by the speakers.